Geographical variation in nest defense among cinereous tit populations in China. Issue 1 (25th March 2023) - Shen, Chao; Yin, Dake; Yu, Jiangping; Zhang, Li; Han, Zheng; Jin, Longru; Liang, Wei; Wang, Haitao
Abstract: Behavioral divergence among populations is common across taxonomic groups, still we know very little about anti-predator behaviors. Animal exposure to predation risk is variable in different ecological contexts. In addition, reproduction value of animals in different geographical regions usually varies. In this study, we tested whether cinereous tits Parus cinereus in different populations exhibited nest defense behaviors similar to those of nest or adult predators and whether their nest defense behaviors showed geographical variation. By using field dummy experiments, we observed tits' nest defense behavior in nest predator common chipmunk Tamias sibiricus and red squirrel Sciurus vulgaris, adult predator Eurasian sparrowhawk Accipiter nisus and nonthreatening species Oriental turtle dove Streptopelia orientalis in the ZJ (44° N), DZ (31° N), and DLS (18° N) populations, respectively. The response scores varied significantly across the 4 dummies in ZJ-tits and DLS-tits but did not in DZ-tits. When facing the chipmunk, ZJ-tits showed the highest response score and DZ-tits showed the lowest response score. When facing the squirrel, ZJ-tits showed a higher response score than tits in the other 2 populations. However, tits among the 3 populations responded similarly to a sparrowhawk or dove with slight response behaviors. In addition, response scores to nest predators were positively correlated with brood size across the 3 populations, but no trend was found for sparrowhawks or doves. Our results indicated that the nest defense behaviors of cinereous tits have evolved in response to large-scale geographical variation in ecological contexts and reproduction value.